PENGARUH KETIMPANGAN PENDAPATAN, INVESTASI DAN PENGANGGURAN TERHADAP PDRB DI PROVINSI SUMATERA UTARA TAHUN 2005-2020 - Jariah Abubakar; Fuji Khairani; Irwan Safwadi (Jurnal Ekonomi Regional Unimal, 2022)
This study examined the effect of inequality on income, investment, and unemployment in North Sumatra Province. This study used secondary data from 2005 to 2020. The data analysis method used was a Multiple Linear Regression with the help of the Eviews 10 program. The results partially indicated that income inequality positively and insignificantly influenced gross regional domestic products in North Sumatra Province, Investment positively and significantly influenced gross regional domestic products in North Sumatra Province. Unemployment negatively and insignificantly influenced gross regional domestic products in North Sumatra Province. Simultaneously, income inequality, investment, and unemployment positively and significantly influenced gross regional domestic products in North Sumatra Province. The magnitude of the effect of Inequality of Investment and Unemployment on Gross Regional Domestic Products in North Sumatra Province was 72.19%, while that of other variables in this model was 27.81%. The government should overcome unemployment to reduce income inequality, mobilize economic sectors and expand investment to increase Gross Regional Domestic Products in North Sumatra Province.